2014
DOI: 10.4049/jimmunol.1401054
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of B Cell Affinity Maturation Explains Enhanced Antibody Cross-Reactivity Induced by the Polyvalent Malaria Vaccine AMA1

Abstract: Polyvalent vaccines use a mixture of Ags representing distinct pathogen strains to induce an immune response that is cross-reactive and protective. However, such approaches often have mixed results, and it is unclear how polyvalency alters the fine specificity of the Ab response and what those consequences might be for protection. In this article, we present a coarse-grain theoretical model of B cell affinity maturation during monovalent and polyvalent vaccinations that predicts the fine specificity and cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(108 citation statements)
references
References 71 publications
2
90
0
Order By: Relevance
“…Luo and Perelson (36) subsequently reported that, during the coevolution of viral strains and Ab responses after infection, Ab breadth increased with the number of variant Ags and the mutational distances separating them. This result likely reflects the fact that, like Chaudhury et al (33), Luo and Perelson (36) assume that there is one conserved epitope shared by all Ags, different Ags contain distinct epitopes composed of variable residues only, and B cells target either the conserved epitope or a variable epitope. The authors considered broadly cross-reactive Abs to be those with high affinity for the conserved epitope.…”
Section: Significancementioning
confidence: 85%
See 2 more Smart Citations
“…Luo and Perelson (36) subsequently reported that, during the coevolution of viral strains and Ab responses after infection, Ab breadth increased with the number of variant Ags and the mutational distances separating them. This result likely reflects the fact that, like Chaudhury et al (33), Luo and Perelson (36) assume that there is one conserved epitope shared by all Ags, different Ags contain distinct epitopes composed of variable residues only, and B cells target either the conserved epitope or a variable epitope. The authors considered broadly cross-reactive Abs to be those with high affinity for the conserved epitope.…”
Section: Significancementioning
confidence: 85%
“…Chaudhury et al (33) studied the generation of protective and cross-reactive Abs against diverse strains of malaria on immunization with a few strains. The malaria apical membrane has a cluster of conserved epitopes (binding targets for B cells) and a cluster of highly variable ones.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Broadly neutralizing antibodies can be thought of as having, on average, more available antigen than narrowly neutralizing antibodies. The idea that antibodies to abundant antigens, such as conserved epitopes, should proliferate more than antibodies to specific epitopes has been used to explain patterns of immunodominance in response to malaria [135] and is consistent with basic principles of population growth. However, the subdominance of anti-stalk antibodies in influenza suggests that structure complicates simple assessments of antigen availability.…”
Section: Vaccines To Direct Evolutionmentioning
confidence: 98%
“…With the exception of occasional mutations, the conserved epitope is common to all viruses. A similar approach has been used to model a malaria vaccine antigen (24). The binding between an epitope and an antibody is determined by the length of the longest common substring between their string representations (25,26) in the absence of any occluding structures, a quantity we call the match length.…”
Section: Significancementioning
confidence: 99%